Problematika Penentuan Status Kalimat dalam Pebelajaran Bahasa Arab - Mas’ud, Moh. Ali; Irawan, Vaesol Wahyu Eka (MOMENTUM : Jurnal Sosial dan Keagamaan, 2022)
Speaking fluently in Arabic can be known by anyone. However, expertise in determining the status of each sentence diction that is composed requires more specialized knowledge, such as mastery of nahwu and nerve disciplines. Students in Higher Education, with a fairly complex background are the main factors of weakness in the acceptance of Nahwu and Nerve discipline materials. One of the discussions in the problem of learning Arabic is determining the status of sentences. This research uses qualitative research methods with the type of Library Research. Data collection uses library books, while data testing uses descriptive analysis. Based on the results of the study can be concluded; weak student knowledge about the signs of each sentence., then weak interest in independent learning, and weak external encouragement of students. To avoid these problems, each student needs to maximize independently or through environmental conditions to support the achievement of competence in determining the status of sentences in Arabic.